Approaching retirement : Social divisions, welfare and exclusion - Mann, Kirk, 1952- (Book collections on Project MUSE., 2001)
Using the idea of the social division of welfare as a template, this book assesses different approaches to retirement pensions policy, highlighting their relative strengths and weaknesses. An invaluable resource for social science students at all levels, and for those who teach them. Economists and pension practitioners will also find food for thought here.